MENSIASATI KELANGKAAN PUPUK ANORGANIK DENGAN ENGGUNAKAN PUPUK ORGANIK BERBASIS LIMBAH PETERNAKAN DAN PERTANIAN DI DESA KAMALU ECAMATAN OGODEIDE KABUPATEN TOLITOLI - Syadik, Fajar; Salawati, Salawati; Sjarifuddin Ende; Sunarti (Bengkulu Institute, 2025)
This Field Work Practice was carried out with the aim of knowing how to apply a transformational leadership style to improve the performance of employees in the Vocational School Development Division of the Bali Province Youth and Sports Education Office. The Office of Education, Youth and Sports is one of the government agencies whose job is to assist and manage the government in activities related to education and sports. In the current era of globalization, government institutions are required to maximize their performance in various ways. The role of this employee's performance can be influenced by the existence of a leadership style because each task given will be optimally achieved if the leader supervises and directs the employee. One of them is the transformational leadership style where this transformational leadership can influence employees to continue to hone their abilities in completing work. Based on the results of student observations, it can be concluded that the Head of the Vocational School Development Division has implemented good transformational leadership so that it is able to improve employee performance and help government institutions to be more advanced and achieve their goals.